(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Livestock farming is an important branch of agriculture and plays a significant role in ensuring food security, economic development, and maintaining agro-ecological sustainability. This study examines the economic, social, and environmental aspects of livestock farming. It also analyzes the role of livestock farming in the agricultural system and its development prospects. Based on local and international experience, necessary measures for the development of livestock farming are proposed.